Pertumbuhan dan hasil tanaman sawi (Brassica rapa L.) sebagai respon terhadap jarak tanam pada dua periode tanam - Saraswati P; Syrylus Keupung; Inna Rumainum; Sutiharni Sutiharni; Fenny Asyerem; Linda E. Lindongi; Marnangon Tambunan; Ni Made Gari (Program Pascasarjana Universitas Papua, 2023)
Mustard consumption increases due to population growth, therefore it is necessary to increase its yield. One of the cultivation techniques to increase the growth and yield of green mustard can be done by the right plant spacing. This study aims to examine several plant spacings in two planting periods on the growth and yield of green mustard. The research was carried out from April to June 2020, at the Experimental Field of Agriculture Faculty Papua University, Manokwari, West Papua. This study was laid in a Randomized Block Design (RAK), with 3 spacing treatments, namely 25 cm x 15 cm, 25 cm x 20 cm and 25 cm x 30 cm. Each treatment was repeated 5 times. The data was analyzed using analysis of variance at the 95% confidence level, and if it had a significant effect, it was continued with the Least Significant Difference Test (BNT) at the 95% level. To see the comparison of mustard yield between the first and second studies, tabulated analysis was used. The results of the first and second studies showed that the three treatments tested had a significant and very significant effect on the character of plant weight per plant, per plot, and yield per hectare. The 25 cm x 15 cm plant spacing resulted in the highest yield per plot or per hectare. Plant spacing of 25 cm x 15 cm was 12 tons/ha produced the highet yield. On the other hand, a spacing of 25 cm x 30 cm produced the highest yield per plant. The growth and yield components decreased in the second study, except at a spacing of 25 cm x 15 cm which capable of producing 10 tons/ha.